Application of artificial intelligence-assisted Traditional Chinese medicine formula granules in bone and joint degenerative diseases in the field of holistic health - Zhang, Xian-Quan; Wei, Xing-De; Gu, Zhuo-Xu; Zhou, Guang-Hui; Huang, Chu-Jia; Luo, Ming-Hui; Zeng, Ling-Feng; Yang, Wei-Yi (Frontiers in Medicine, 2025)
As global aging intensifies, the incidence of degenerative bone and joint diseases such as osteoarthritis bone aging and osteoporosis continues to rise. Traditional treatment methods face bottlenecks in long-term management, including drug side effects and low patient compliance. Traditional Chinese medicine (TCM) formula granules, which utilize plant-based natural products, show excellent clinical efficacy in managing these conditions. With the development of technology, artificial intelligence (AI) technology has enhanced the clinical efficacy of TCM formula granules through multiple approaches such as intelligent syndrome differentiation and formula optimization, drug efficacy prediction and mechanism analysis, as well as patient management and therapeutic effect monitoring, providing a new approach for the prevention and treatment of complex degenerative diseases. This paper systematically reviews the core advantages of TCM formula granules and their suitability for orthopedic diseases such as bone aging and osteoporosis. It analyzes the application models of AI technology in optimizing TCM formula granules, predicting drug efficacy, and personalized treatment. The main research results show that the artificial intelligence-driven TCM formula granule system is beneficial for promoting the full-cycle integration of “prevention - treatment - rehabilitation” in the chronic disease management of bone and joint degenerative diseases. However, challenges persist in clinical evidence standardization, algorithm interpretability, and ethical frameworks. Future directions require interdisciplinary technological innovation, policy-industrial synergy, and global collaboration to advance intelligent TCM transformation for degenerative disease management.